Perilaku Fear Of Missing Out (FOMO) Dalam Konsumsi Di Kalangan Mahasiswa FEBI UINSU Ditinjau Dalam Prespektif Maslahah - Riska Syahputri Nasution; Sugianto Sugianto; Budi Dharma (UNIVED Press, 2023)
This study highlights the complexity of FOMO behavior in fashion consumption among students at the Faculty of Islamic Economics and Business, North Sumatra State Islamic University (FEBI UINSU), taking into account the maslahah perspective in Islam. Using a phenomenological research method with an exploratory qualitative approach, data was obtained through Systematic Literature Review (SLR), interviews and observations of 97 students. The research results show that dependence on social media has influenced the way students spend their time and make their consumption decisions. FOMO is a major driver of online activity, with celebrities, influencers and personal role models having a huge influence in shaping their fashion preferences. Students often feel anxious if they are not involved in current trends on social media. However, there is awareness of the negative impact of consumer behavior triggered by FOMO, which encourages some students to prioritize needs over wants in their consumption. This research highlights the importance of awareness of the influence of social media and developing self-control in dealing with consumer behavior. As students study the principles of Islamic economics, they are expected to apply these principles in their daily lives to manage fashion consumption wisely and responsibly.